On a straight line, the sum of the angles is \(180^\circ\). Given the two angles are \(2x + 3\) and \(x - 6\), we can set up the equation:
\[ (2x + 3) + (x - 6) = 180 \]
Now, simplify the equation:
\[ 2x + 3 + x - 6 = 180 \]
Combine like terms:
\[ 3x - 3 = 180 \]
Now, add \(3\) to both sides:
\[ 3x = 183 \]
Next, divide by \(3\):
\[ x = 61 \]
Now we can find the measures of the two angles by substituting \(x\) back into the expressions for the angles.
- For the angle \(2x + 3\):
\[ 2(61) + 3 = 122 + 3 = 125 \]
- For the angle \(x - 6\):
\[ 61 - 6 = 55 \]
Thus, the measures of the two angles are:
- \(125^\circ\)
- \(55^\circ\)
These satisfy the condition that their sum is \(180^\circ\) (125 + 55 = 180).